Financial Determinants of Corporate Tax Planning among Malaysian Listed Companies in Trading and Services - Zainazor, Zafierah; Nasir, Noor Emilina Mohd; Rashid, Norfadzilah; Awang, Yunita (Indonesian Journal of Sustainability Accounting and Management, 2023)
Corporate Tax Planning was identified as one of the activity routes to creative accounting strategies in the prior literature review as well as a mechanism used by the companies to reduce tax liabilities. The purpose of this study is to investigate the relationship between capital intensity, leverage, audit quality, and financial distress as the financial determinants of corporate tax planning, proxied by effective tax rates. The study used the financial data retrieved from Thomson Data stream which consists of 43 Malaysian Listed Companies in trading and services for six years period from 2016 to 2021. The final sample of 258 firm-year observations was analyzed using fixed effect model regression. This study reveals that capital intensity, leverage, and audit quality have a significant relationship with the effective tax rate. Thus, it can be concluded that financial variables and external monitoring are able to influence the level of corporate tax planning.